Acetazolamide attenuates chemical-stimulated but not thermal-stimulated acute pain in mice - Sun Ya-jie; Chen Ying; Pang Chong; Wu Ning; Li Jin (Acta Pharmacologica Sinica, 2016)
Ya-jie SUN§, Ying CHEN, Chong PANG, Ning WU*, Jin LI* Department of New Drug Evaluation, Beijing Institute of Pharmacology and Toxicology, Beijing 100850, China Aim: Acetazolamide (AZA), a carbonic anhydrase (CA) inhibitor, has been found to alleviate inflammatory and neuropathic pain in rats. In the present study, we investigated the effects of AZA on thermal- and chemical-stimulated acute pain in mice and the possible mechanisms underlying the effects. Methods: Five acute pain models based on thermal and chemical stimuli were established to investigate the effects of AZA on different types of nociception in mice. The antinociceptive effects of methazolamide (another CA inhibitor) and diazepam (a positive allosteric modulator of GABAA receptor) were also examined. The drugs were administered either intraperitoneally (ip) or intrathecally. Results: AZA (50–200 mg/kg, ip) did not produce analgesia in two thermal-stimulated acute pain models, ie, mouse tail-flick and hot-plate tests. In contrast, AZA (50–200 mg/kg, ip) dose-dependently reduced paw licking time in both capsaicin and formalin tests in mice. A similar result was observed in a mouse acetic acid-induced writhing test. However, AZA (10 nmol/mouse, intrathecally) did not produce significant analgesia in the 3 chemical-stimulated acute pain models. In addition, methazolamide (50–200 mg/kg, ip) and diazepam (0.25–1.0 mg/kg, ip) did not produce significant analgesia in either thermal- or chemical-stimulated acute pain. Conclusion: AZA produces analgesia in chemical-stimulated, but not thermal-stimulated acute pain in mice. The attenuation of chemical-stimulated acute pain by AZA may not be due to enhancement of GABAA receptor-mediated inhibition via inhibiting CA activity but rather a peripheral ion channel-related mechanism. Keywords: acetazolamide; methazolamide; diazepam; analgesia; tail-flick test; hot-plate test; capsaicin test; formalin test; acetic acid-induced writhing test; carbonic anhydrase; GABAA receptor This work was supported by the National Natural Science Foundation of China (Grant No 81171046). § Now at Beijing Institute of Microbiology and Epidemiology, Beijing 100071, China * To whom correspondence should be addressed. E-mail jinli9802@163.com (Jin LI); wuning7671@126.com(Ning WU) Received 2013-05-05 Accepted 2013-09-18